Prioritising Storage Practices: A New Approach to Housing Design Thinking - Marco, Elena; Williams, Katie; Oliveira, Sonja (Interiority, 2021)
Inhabitants of UK housing have more possessions than ever, whilst space for living in standardised houses is at a premium. The acquisition of material possessions, and how it affects both space and inhabitants’ wellbeing, has not previously been considered in architectural practice or housing policy research fields. This paper addresses this gap, by exploring how practising architects design for the storage of material possessions in housing. For the first time, it places storage practices at the centre of housing design thinking, by engaging practising architects in a design intervention to explore original design solutions that support inhabitants’ lives and lifestyles, and therefore their wellbeing. The study uses a new storage-focused conceptual design framework to seek design knowledge, to better understand how storage practices could be considered when designing. The findings have implications for design practice research, providing an account of how architects consider storage in housing design, drawing on novel design intervention methods.